Empire, the sea and global history Britain's maritime world, c. 1760-c. 1840 - Cannadine, David (Palgrave Macmillan, 2007)
Between the end of the Seven Years war in 1763, and the abolition of slavery within its Empire in 1833, Britain's maritime engagement with the wider world was transformed. They were originally delivered as lectures in a series jointly sponsored by the Institute of Historical Research and by the Centre for Imperial and Maritime Studies at the National Maritime Museum.